2003
DOI: 10.1007/s00125-002-0895-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of regulatory elements in the human adipose most abundant gene transcript-1 (apM-1) promoter: role of SP1/SP3 and TNF-? as regulatory pathways

Abstract: Aims/hypothesis. The human adipocyte-specific apM-1 (adipose most abundant gene transcript-1) gene encodes for a secretory protein of the adipose tissue that seems to play a role in the pathogenesis of obesityrelated insulin resistance and its expression is inhibited by TNF-α. Our aim was to characterize the tissuespecific regulation of the recently cloned apM-1 promoter and the mechanisms of TNF-α-induced downregulation of the apM-1 gene. Methods. We characterised the apM-1 gene by electrophoretic mobility sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Of note, it has been reported that C/EBP␣ up-regulates adiponectin expression through a C/EBP consensus sequence at the human adiponectin promoter (29). Although a putative C/EBP␣ binding site in the murine adiponectin promoter can be found by sequence scan, most studies did not demonstrate binding of C/EBP␣ to this site (14,26,30). Our study indicated that C/EBP␣ and Foxo1 up-regulate adiponectin promoter activity in a synergistic manner.…”
Section: Foxo1mentioning
confidence: 55%
“…Of note, it has been reported that C/EBP␣ up-regulates adiponectin expression through a C/EBP consensus sequence at the human adiponectin promoter (29). Although a putative C/EBP␣ binding site in the murine adiponectin promoter can be found by sequence scan, most studies did not demonstrate binding of C/EBP␣ to this site (14,26,30). Our study indicated that C/EBP␣ and Foxo1 up-regulate adiponectin promoter activity in a synergistic manner.…”
Section: Foxo1mentioning
confidence: 55%
“…It is well known that AdipoQ abundance is inversely associated with obesity, insulin resistance and type 2 diabetes, inflammatory markers, and endothelial dysfunction as well as with the development of cardiovascular disease (37). The production of AdipoQ by adipocytes is controlled at the level of gene expression through specific promoter regions (38) as well as by epigenetic mechanisms (28). Histone modifications of the AdipoQ gene were examined in mice exposed to a maternal high-fat diet (HFD) (39), and increased DNA methylation in the AdipoQ promoter region was reported in mice fed an HFD during late gestation (35).…”
Section: Discussionmentioning
confidence: 99%
“…SNP rs182052 is located in intron 1 of ADIPOQ gene, and its minor allele A results in a loss of a Sp1-binding site and gain of a CCAAT/enhancer-binding protein (C/EBP) b-binding site, reducing adipocyte differentiation3839. SNP rs182052 was reported to be significantly associated with lower plasma adiponectin40, a strong predictor of diabetes41, which was reflected in our finding that cases had lower adiponectin levels than controls (Fig.…”
Section: Discussionmentioning
confidence: 53%